Enhancement of key chemical constituents in Aquilaria malaccensis lamarck (karas) through in vitro polyploidization - A. Rahman, Siti Suhaila (2017)
Aquilaria malaccensis is a highly valued timber species in Malaysia for its ability to produce fragrant resin known as agarwood. The agarwood consists of volatile chemical (sesquiterpenoid groups and phenyl ethyl chromones derivatives), reported to be triggered as a defence mechanism due to attacks by microorganisms at the wounded areas. In the natural forest, only up to 10% of the wild A. malaccensis were found to be able to produce agarwood. Malaysia is currently facing threats of A. malaccensis extinction due to illegal harvesting of the species which have caused this species to be listed in CITES (Appendix II). In view of this situation, there is a need to develop A. malaccensis clones with enhanced chemical constituents for commercial plantation. The in vitro polyploidization has been proven to improve desired characteristics in plant such as fast growing, increased in bioactive compounds and secondary metabolites. Therefore, the objectives of this study were to develop in vitro polyploidization protocol in A. malaccensis; to determine the morphological characteristics difference between the polyploids to its diploid counterparts and; to evaluate and compare the chemical constituents in the different ploidy levels of A. malaccensis. The A. malaccensis in vitro polyploidization was carried out using antimitotic agents (colchicine and trifluralin) at different concentrations and exposure times on two types of explants (shoot tip and nodal segment). The ploidy levels of the in vitro induced polyploid plantlets were determined using flow cytometer, chromosome count and stomata size measurement. Diploid plantlets were used as reference. The plant height, leaf length and leaf width were also measured in tetraploids and diploids plantlets. The chemical profiling of the in vitro induced polyploids and diploids plantlets were evaluated using the Headspace-Solid Phase Microextraction (HS-SPME) and hydro distillation, HD (for essential oil extraction, if any);both coupled with gas chromatography-mass spectrometry (GC/MS).The experiment showed that A. malaccensis polyploids can be induced with tetraploids obtained using nodal segments treated with 0.1 mM trifluralin for 120 hours. However, other treatments were only able to induce mixoploids in shoot tip (treated with 1 mM colchicine at 24 and 120 hours exposure time; 2 mM colchicine at 48 hours exposure time; while 0.05 mM and 0.1 mM trifluralin both at 120 hours exposure time) and nodal segment (0.05 mM trifluralin at 120 hours exposure time). The DNA content and genome sizes were quantified as 1.84 pg 2C-1 and 899 Mbp in the diploid and, 3.86 pg 2C-1 and 1887 Mbp in the tetraploids. A. malaccensis chromosome number was determined to be 2x=14 (diploids), and 4x=28 (tetraploids). The tetraploids showed larger stomata guard cell sizes (33.3±0.6 μm) in leaves as compared to diploids (23.1±0.5μm). Plant height of 24 months old tetraploids were 49±0.05 cm, more than double the height of diploids, stem diameter of tetraploids were 0.7±0.02 cm compared to 0.5±0.02 cm in diploids, the leaf area also doubled in size compared to diploids, with 24.07±0.04 cm2 in tetraploids leaf sample. Chemical profiling of four different sources were compared: seedling grown under normal conditions, seedling grown in vitro, in vitro diploids and in vitro tetraploids. Through HS-SPME/GCMS, highest amount of important sesquiterpenes (volatile chemical constituents in agarwood oil from mature trees) such as α-eudesmol and α-guaiene, was found in stem and root samples of in vitro tetraploids. The HD-GC/MS method showed all samples did not contain essential oil. However, 60% of the hydrosol water from leaves and 49.1% of the residual water from root samples of in vitro tetraploids consists of important sesquiterpenes. Further evaluation in A. malaccensis diploid and tetraploid plants at 24 months old showed fewer amounts of chemical constituents than the 4 months old in all plant parts. The tetraploids root however, contains important sesquiterpene, α- guaiene (2.92%), which was not detected in diploids. These results demonstrated that A. malaccensis polyploid plantlets can be induced for plant improvement. The A. malaccensis tetraploids contained higher chemical constituents which can be promoted as high quality A. malaccensis clones for commercial plantation.